Associations between local haemodynamics and carotid intraplaque haemorrhage with different stenosis severities: A preliminary study based on MRI and CFD. (August 2019) - Dai, Yuanyuan; Qian, Yi; Zhang, Mingzi; Li, Yujie; Lv, Peng; Tang, Xiao; Javadzadegan, Ashkan; Lin, Jiang
Highlights: 59 carotid atherosclerosis patients have been performed MRI and CFD to estimate the haemodynamics under various stenosis. All patients were categorised to groups; IPH and non-IPH. Each group was classified to 3 subgroups by the stenosis class. mWSS was selected to compare from two groups, statistic studies were performed to analyse the difference between them. The results indicated mWSS was associated at mild stenosis. However, it didn't show significant increase in the severe. The MRI and CFD may provide quantitative diagnosis to estimate carotid plaque volume, and thereby predict stroke risks. Abstract: The relationship between carotid blood flow and carotid intraplaque haemorrhage (IPH) is not fully understood. This study was to investigate the relationship between local haemodynamics and carotid plaques with IPH associated with severe artery stenosis. Fifty-nine patients with carotid atherosclerosis were enrolled in this study and underwent magnetic resonance imaging (MRI) measurement. IPH and non-IPH compositions were differentiated based on plaque sequences. Haemodynamic simulations were performed by using computational fluid dynamics (CFD). All the carotids were categorised into IPH and non-IPH groups. In each group, the artery stenosis was divided into mild (<50%), moderate (50–70%) and severe (>70%) subgroups. Maximum wall shear stress (mWSS) was calculated and comparisons made between IPH and non-IPH groups using independent t -test. Furthermore, the relationship between mWSS and IPH volume was examined using Pearson's correlation. The mWSS result calculated from the IPH group was significantly higher than that of the non-IPH group; at mild stenosis (P = 0.001) and moderate stenosis (P = 0.002) respectively. However, there was no significant difference in cases of severe stenosis (P = 0.42). Furthermore, the results showed a positive correlation between mWSS and IPH volume (r = 0.763, P < 0.001) in the cases of stenosis of less than 70%. mWSS was found to be significantly associated with IPH for carotids with stenosis of less than 70%. This highlights that mWSS is a potential quantitative parameter for the risk diagnosis of the carotid atherosclerosis.